Overview of the central sterilization supply department, an integral part of the hospital - Bal, Brijesh; Balaraju, Anitha (The Journal of Infection in Developing Countries, 2025)
Introduction: The central sterile supply department (CSSD) is an integrated unit in a hospital that facilitates the sterilization process. Sterilization destroys all bacteria, viruses, spores, and other microorganisms from the surface of medical devices and supplies, including fluids, which cause the spread of infection when used during patient care. This department sterilizes reusable medical devices, linen, and surgical instruments by physical or chemical methods. Methodology: We adopted a systematic literature review method for this study. There are few comprehensive studies on the CSSD. This extensive review of CSSD is based on information retrieved from scientific databases (Google Scholar and Web of Science) and grey literature from organizations. All publications on safe and feasible methods of disinfection and sterilization processes in hospitals were reviewed. Information on workflow, responsibilities, infection prevention control (IPC) protocols, physical requirements, staffing requirements, and any special equipment used in the process of sterilization were reviewed. Results: About 300 articles were identified and relevant articles were selected for this review. The information was summarized to guide optimal standard settings for sterilizing reusable items in the CSSD. Special emphasis was given to identifying any unique methods or resource-demanding techniques of disinfecting and sterilizing, and any predefined layout that may facilitate maximum IPC and hygiene. Conclusions: This comprehensive review of the literature may serve as a guide for hospital IPC.